2013
DOI: 10.1097/bsd.0b013e31826e0ca4
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative Grade Affects the Responses of Human Nucleus Pulposus Cells to Link-N, CTGF, and TGFβ3

Abstract: Study Design Cells isolated from moderately and severely degenerated human intervertebral discs (IVDs) cultured in an alginate scaffold. Objective To compare the regenerative potential of moderately vs. severely degenerated cells using three pro-anabolic stimulants. Summary of Background Data Injection of soluble cell signaling factors has potential to slow the progression of IVD degeneration. While degenerative grade is thought to be an important factor in targeting therapeutic interventions it remains un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 34 publications
1
27
1
Order By: Relevance
“…The regenerative potential of Link-N has been studied in many systems (Mwale et al, 2003;Mwale et al, 2011;Antoniou et al, 2012;Abbott et al, 2013), and in the present study human disc cells from NP and AF in their microenvironment, under the influence of Link-N, showed increase in aggrecan synthesis and downregulation of proteases by NP cells. In contrast, recent work by Abbott et al (Abbott et al, 2013) evaluated the effect of Link-N, CTGF and TGF-β + Dex on human disc cells in alginate.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The regenerative potential of Link-N has been studied in many systems (Mwale et al, 2003;Mwale et al, 2011;Antoniou et al, 2012;Abbott et al, 2013), and in the present study human disc cells from NP and AF in their microenvironment, under the influence of Link-N, showed increase in aggrecan synthesis and downregulation of proteases by NP cells. In contrast, recent work by Abbott et al (Abbott et al, 2013) evaluated the effect of Link-N, CTGF and TGF-β + Dex on human disc cells in alginate.…”
Section: Discussionsupporting
confidence: 61%
“…In contrast, recent work by Abbott et al (Abbott et al, 2013) evaluated the effect of Link-N, CTGF and TGF-β + Dex on human disc cells in alginate. The study did not show much upregulation of aggrecan by disc cells exposed to Link-N compared to other experimental groups.…”
Section: Discussionmentioning
confidence: 95%
“…TGF-β has been reported to increase proteoglycan production to adjust the proliferation of type II collagen intervertebral disk cells and reduce matrix degradation to thereby regulate the metabolism of intervertebral disc cells (33,34). While certain studies found that proteoglycan production in nucleus pulposus cells was increased through gene therapy with TGF-β, it is inferred that TGF-β is a protective cytokine in the intervertebral disc (35)(36)(37). In the present study, an increasing trend of TGF-β1 at 1 month post-operation was identified, while it had significantly decreased at 3 months.…”
Section: Control Groupcontrasting
confidence: 41%
“…Additionally, considering that mechanotransduction through ␣5␤1 integrin is altered in degenerate NP cells, it is also likely that binding of CCN2 to this cognate integrin fails to have the same anabolic/anti-catabolic effect that it does in healthy discs. In fact, in terms of catabolic gene expression and matrix production, recent studies confirm that NP cells from severely degenerated discs respond less robustly to anabolic factors, including CCN2 and TGF-␤, than healthy or moderately degenerated cells (49,50). Further experiments measuring catabolic gene expression after treatment of degenerate or nondegenerate human NP cells with IL-1␤, CCN2, or a Healthy NP Degenerate NP FIGURE 8.…”
Section: Discussionmentioning
confidence: 95%